FORMULASI DAN UJI AKTIVITAS ANTIBAKTERI SEDIAAN DEODORAN SPRAY EKSTRAK ETANOL DAUN KUPU-KUPU (Bauhinia purpurea L) TERHADAP Staphylococcus epidermidis DAN Pseudomonas aeruginosa - Humaira, Yara; Nasution, Muhammad Amin; Yuniarti, Rafita; Nasution, Haris Munandar (Acta Pharmaceutica Indonesia, 2025)
Body odor affects a person's social relationships, unpleasant odors are caused by bacteria that appear on parts of the body that are from sweat. One of the cosmetic products that is believed to prevent body odor is deodorant. Deodorant  spray has more hygiene because it is used without direct contact with the skin. An important component in deodorant sprays formulation is antimicrobial agents. Long-term use of synthetic antimicrobials can lead to resistance, so it must to use natural antimicrobials. Butterfly leaves (Bauhinia purpurea L) can be a natural antimicrobial agent, because  contain secondary metabolites such as flavonoids, phenols, alkaloids and saponins that can inhibit bacterial growth. This research began with phytochemical screening, making deodorant spray F0 (without extract), F1 (10% ), F2 (15% t), and F3 (20%) extract, evaluation and testing of antibacterial activity against Staphylococcus epidermidis dan Pseudomonas aeruginosa. The data analyzed with SPSS using One Way ANNOVA method. The results of this study showed that the pH value decrease along with the increase in the concentration of the extract in the preparation, but it was still within the normal pH range of 4.5-6.5. The results of the irritation test did not show an irritation and the preparation was preferred by the panelists. The antibacterial activity of deodorant spray  against both bacteria has a strong inhibitory power, there are F0 (0 mm), F1 (12.92 mm), F2 (13.82 mm), and F3 (16.85 mm) against Staphylococcus epidermidis, and F0 (0 mm), F1 (12.57 mm), F2 (13.47 mm), and F3 (15.32 mm).